Design and fabrication of annular arrays for high-frequency ultrasound - Brown, Jeremy A (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2004)
The design, fabrication, and performance of miniature high-frequency annular arrays are described. A 50-MHz, 2-mm-diameter, 7-element, equal-area annular array was fabricated and tested. The array elements were defined using photolithography and the electrical contacts were made using ultrasonic wire bonding. The resulting transducer produced pulses with a -6 dB bandwidth of 52% and an insertion loss of -16 dB. A radiation pattern was collected by scanning the transducer array above the tip of a glass fiber. A -6 dB two-way beam width of 75 microns was found at f/2. The radiation pattern decreased smoothly to less than -60 dB at a distance of 550 microns